The role of maternal effect in horse breeding - Győri , Piroska Andrea; Abayné Hamar, Enikő; Nyerges-Bohák, Zsófia (Animal welfare, Ethology and Housing Systems (AWETH), 2024)
Horse breeding begins with defining the specific breeding goal. The appearance and temperament developed during the decades – and even centuries in case of many breeds – through the breeding work determine the area in which the specific breed can be used successfully. The use of the appropriate breed and the accurate knowledge of the given stock are essential in successful breeding work. The maternal effect is a significant factor in the practice of horse breeding. It is a genetic principle that a mediocre offspring of an outstanding mare family has a higher breeding value than a plus variant offspring of a weak family. Understanding and objectively studying the mare’s effect may provide relevant information and knowledge for the breeder. The mare greatly determines the appearance and behavioural traits of the offspring through genetic and maternal factors. Through the adequate mare population valuable characteristics may be preserved and maintained in a stock. Studying the maternal effect may be a tool for farms to develope their stock according to specific plans and criteria in order to be able to successfully breed horses that meet the breeding and market requirements. For successful breeding work, it is not enough to use an outstanding stallion the quality of the mare family. Namely, it is essential to select mares suitable for the breeding goals, thereby providing a strong foundation for the breeding stock.
Keywords: genetics; horse breeding; maternal effect; selection